PERANAN PEJABAT PEMBUAT AKTA IKRAR WAKAF DALAM MENCEGAH TERJADINYA SENGKETA TANAH WAKAF - Zahran Rafid; Hardianti Yusuf (IAIN BONE, 2020)
AbstractThis study discusses the role of officials maker of the waqf pledge deed to prevent the occurrence of waqf land disputes, which occurred in the Tanete Riattang Barat District Area. This research uses mixed methods, namely library research and field research. Data was collected through direct interviews with informants PPAIW, namely the Head of Religious Affairs Office (KUA) and the public who were aware of the waqf land dispute in the Tanete Riattang Barat District Area.The results showed the role of PPAIW in preventing the occurrence of waqf land disputes was very important. Therefore, PPAIW was tasked to make the waqf pledge deed and the waqf land certificate. With the deed and certificate, it would narrow the chances of a waqf land dispute. Besides making endowment pledges and endowment land certificates, the next step was to bring the two disputing parties together and provide an understanding of the disputed waqf land and show the evidence that had been made by PPAIW itself.Keywords : Certificate Waqf; Deed Pledge of Waqf; Officials Maker of the Waqf Pledge Deed (PPAIW).